GE_GERICHTE P/21676/2019 vom 11. August 2022 - GE Cour de justice (2022)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;CALOMNIE;OUVERTURE DE LA PROCÉDURE;DÉFENSE D'OFFICE;ACTION PÉNALE;PRESCRIPTION;DÉNONCIATION CALOMNIEUSE | CPP.310; CPP.312; CP.174; PPMin.25; DPMin.36.al1.leta; CP.303.al1